Familial hypercholesterolaemia patient support groups and advocacy: A multinational perspective. (October 2018) - Payne, Jules; Williams, Simon; Maxwell, Diana; Pariente, M Teresa; Olivares, Raquel Arroyo; Janssen ten Haaf, Marlieke; Wong-Rieger, Durhane; Rieger, Fritz; Covato, Angela; Wong-Rieger, Hilary; Cermakova, Luba; Wilemon, Katherine
Abstract: Familial hypercholesterolaemia (FH) is an autosomal-dominant disorder associated with high low-density lipoprotein cholesterol (LDL-C). Left untreated, 50% of men with FH will develop coronary heart disease by the age of 50 and 30% of women by the age 60 [1, 2]. It is estimated that the prevalence may be as high as one in 250 people, with most undiagnosed. This article explores the development of advocacy in FH patient organisations, citing examples from Canada, the Netherlands, Spain, the US and the UK as well as the pan-European patient organisation, FH Europe. The article demonstrates that for patient advocacy, the link with medical and scientific expertise is essential to ensure that advocacy for familial hypercholesterolaemia is well-founded and credible and that patient associations are prepared to take a long-term view on achieving improvements in identification and treatment. Highlights: Familial hypercholesterolaemia (FH) is mostly an unidentified disease that does not discriminate. More awareness is required to increase the number of FH patients identified. Patient empowerment and the patient voice is paramount in raising awareness and getting system change to identify and optimally treat all FH cases. Patient organisations and healthcare professionals work together to find all FH patients worldwide, the earlier the better. Networking by and between FH patient organisations is important to share information and learning.